Acoustic investigation of complex seabeds - Guigné, J. Y.; Blondel, Philippe (Springer, 2017)
Offshore drilling and constructions require exact knowledge of the geophysical properties of the seabed and sub-seabed, as unexpected objects can slow down or halt projects. This book presents the state-of-the-art in acoustic exploration of the seabed and sub-seabed, from initial designs in the 1980s to commercial contracting and operation of the Acoustic CorerTM in the last decade. The Acoustic CorerTM is a high-definition commercial acoustic sub-bottom imaging system, producing an "acoustic core" within which sub-seabed sedimentary characteristics and discrete buried objects larger than 0.5 m can be identified and mapped. It makes use of the innovative JYG-cross design, inspired by seismic reflection and uses Synthetic Aperture Sonar (SAS) multi-angle scattering in and within the seabed to deliver unprecedented imagery. This book was written by the inventor of these concepts, a known specialist in seabed acoustics, with help from an experienced academic and author. It is intended first and foremost as a "how-to" guide for offshore industries looking at techniques to make the installation of different types of structures safe and efficient.- Resumé vydavatel
Keywords: mořské dno; oceánografie; akustika; sea floor; oceanography; acoustics; elektronické knihy; monografie; electronic books; monographs